РАРИТЕТНІ ВИДИ В ОРНІТОКОМПЛЕКСАХ СОЛОНЧАКОВИХ ПОДІВ ТА ЇХ ВНЕСОК У ПІДТРИМКУ БІОРІЗНОМАНІТТЯ (ПІВНІЧНО-ЗАХІДНЕ ПРИАЗОВ'Є) - КОШЕЛЄВ Василь Олександрович (Zenodo, 2018)
Characteristic elements of the seaside landscapes of the south of Ukraine are saline sands depressions -pods along the banks of estuaries, in the valleys of small rivers, in the place of dried ponds. According to the nature of the vegetation and the animal population, saline sands are referred to the azonal type of the landscape. The combination of different microstations and the abundance of feed in the spring-summer period is causes on them a high species diversity of birds. On saline sands have been noted 180 species of birds, incl. 40 species have included in the red book of Ukraine - in 1988-2018 y. Nesting ornithocomplexes include 36 species, the basis of which are waders and terns. In the high-water seasons, when saline sands are flooded, islands form on the lakes, Charadriiformes and Anatidae nest on them with high density. Each species are prefers certain microstations with characteristic hydrological indices and the nature of the vegetation. Deprived of vegetation and poorly overgrown areas with low vegetation have nests Glareola pra-tincola, Charadrius alexandrinus, Haemantopus ostralegus, Recurvirostra avosetta, Sterna albifrons; in the areas of medium degree of overgrowing (the size of the projective cover of vegetation is up to 30-80%) have nest Vanellus vanellus, Tringa totanus, Alauda arvensis and Himantopus himantopus are nesting in moist meadows. A field lark (Alauda arvensis) and a marsh owl (Asio flammeus) are occuping by steppe areas with dense vege-tation. Such islands on saline sands tributaries are distinguished by maximum species diversity and a high num-ber of nesting birds. Saline sands play an important role in maintaining the number and conservation of rare and endangered species of bird-stenotopes included in the national red book of Ukraine (Asio flammeus, Haemantopus ostra-legus, Charadrius alexandrinus, Glareola pratincola, Recurvirostra avosetta, Himantopus himantopus, Bur-ghinus oedicnemus), and also, the regionally rare species (Charadrius dubius, Tadorna tadorna, etc.). Sharp ...